Occurrence and formation of endogenous histidine hexa-coordination in cold-adapted hemoglobins - MERLINO, ANTONELLO; MAZZARELLA, LELIO; VERGARA, ALESSANDRO; B. Howes; C. Verde; G. di Prisco; G. Smulevich (IUBMB Life, 2011)
Spectroscopic and crystallographic evidence of endogenous (His) ligation at the sixth coordination site of the heme iron has been reported for monomeric, dimeric, and tetrameric hemoglobins (Hbs) in both ferrous (hemochrome) and ferric (hemichrome) oxidation states. In particular, the ferric bis- histidyl adduct represents a common accessible ordered state for the β chains of all tetrameric Hbs isolated from Antarctic and sub-Antarctic fish. Indeed, the crystal structures of known tetrameric Hbs in the bis-His state are characterized by a different binding state of the α and β chains. An overall analysis of the bis-histidyl adduct of globin structures deposited in the Protein Data Bank reveals a marked difference between hemichromes in tetrameric Hbs compared to monomeric/dimeric Hbs. Herein, we review the structural, spectroscopic and stability features of hemichromes in tetrameric Antarctic fish Hbs. The role of bis-histidyl adducts is also addressed in a more evolutionary context alongside the concept of its potential physiological role.